FRI0102 A Systematic Literature Review of the Impact of Comorbidity on Quality of Life and Costs in Patients with Rheumatoid Arthritis. the Gecoar Study. (10th June 2014) - Villaverde, V.; Loza, E.; Ortiz, A.; Martínez-Lόpez, J.A.; Toledano, E.; Lajas, C.; Castañeda, S.
Abstract : Background: In rheumatoid arthritis (RA), comorbidity might alter survival, delay diagnosis and influence treatment decisions. Moreover managing care for patients with several chronic conditions currently represents one of the greatest challenges to rheumatologists. Knowing the impact of specific comorbidities on patient related outcomes may help us prioritize comorbidities in RA when developing general strategies to manage them. Objectives: To examine the impact of comorbidity on quality of life and costs in RA. Methods: A systematic literature review was performed by 2 reviewers, a librarian and a methodologist. Studies were identified by sensitive search strategies in the main bibliographic databases (Medline, Embase and Cochrane Library) up to May 2013. We selected articles that analyzed, in RA patients, the impact of comorbidity (co-existent diseases and complications of RA or associated therapies) on quality of life (QoL) and/or cost. Any type of study except case series or case reports was eligible.Two reviewers (VV and EL) screened the titles and abstracts of the retrieved articles independently. VV reviewed the selected articles in detail and collected the data from the studies included by using ad hoc standard forms. A hand search was completed by reviewing the references of the included studies. An ad hoc risk of bias scale was used. The level of evidence for each comorbidity was assessed with the Oxford Centre for Evidence-based Medicine Levels of Evidence for descriptive/prognostic questions. Results: Of 2.123 citations, 18 were included: 14 studies assessed the impact of comorbidity on QoL and 6 on costs. The most analyzed comorbidities were overall comorbidity, obesity, fibromyalgia and anemia. The risk of bias of studies that assessed global comorbidity and obesity was low; in the rest of studies was moderate-high. Cost publications examined solely direct costs except for one that evaluated indirect costs as well. The risk of bias of cost studies was low. RA patients with comorbidity reported worse quality of life, especially for those with ≥2 comorbid conditions. The level of evidence for specific comorbidities and their impact on QoL was as follow: overweight/obesity (1c); psychiatric and related diseases (2c for anxiety and depression and 3a for fibromyalgia); RA patients with cardiovascular disease, hypertension and diabetes reported worse impact on quality of life and a higher annual progression of HAQ score than RA patients with lung disease, psychiatric or gastrointestinal disease (1c). Patients with RA and comorbidity incurred higher expenses than patients without comorbidity. Patients with cardiovascular disease reported higher costs than those with depression (level of evidence 3b). Conclusions: RA patients with comorbidity, especially those with ≥2 comorbidities have worse quality of life and higher annual progression of HAQ score than RA patients without any comorbidity. Further work is needed to define which comorbidities have more impact on RA costs. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2815